Model Pembelajaran Al Qur’an Hadis Materi Huruf Hijaiyah Pada Siswa Speech Delay Kelas 1 Mi Darul Hikmah Sidoarjo - Arofah Tis’ina, Nur (AL MURABBI, 2023)
Children's communication skills start from the reaction to the sound or voice of their father's mother, even at the age of 2 months the child can show a social smile to everyone to interact. At the age of 18 months, children begin to be able to understand and express 20 meaningful words. Starting at the age of 2 years began to be able to say 1 sentence consisting of 2 words "mama go". Of these 3 aspects, if the child cannot do it, it is said to be late in speaking (Speech Delay). The main purpose of the study was to detect the growth and development of Speech Delay students in MI Darul Hikmah Prasung. The obstacle that occurred in this study was that they had difficulty in understanding hijaiyah letters. The type of research used is qualitative research. The results of research on the process of implementing Qur'an Hadith Learning in Students Speech Delay Hijaiyah Letter material must use a loud and repetitive voice so that students focus more on what has been conveyed by the teacher. If the delivery of material to Speech Delay students is not appropriate, then the student is less focused on receiving the material and gets bored quickly. So that in the implementation of learning, teachers use several approaches and use learning media to attract more attention to speech delay students, namely with the media of hijaiyah punctuation balls. From this media has competency standards used in the implementation of learning, namely: (1) Direct Method (direct method), (2) Repeatation (repeated). (3) Sincere affection.